1988
DOI: 10.2337/diacare.11.10.787
|View full text |Cite
|
Sign up to set email alerts
|

Putative Determinants of Arterial Wall Compliance in NIDDM

Abstract: Aortoiliac arterial wall compliance was measured in apparently healthy subjects and in patients with non-insulin-dependent diabetes (NIDDM), on diet alone, who had no clinical evidence of peripheral arterial disease. Compliance was significantly lower in patients with diabetes. The two clinical groups were combined to provide as wide a range of blood glucose values as possible. After allowing for the influence of age, there were significant negative correlations between compliance and free fatty acid and insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
3
2

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 12 publications
1
25
3
2
Order By: Relevance
“…In focusing on contributors for accelerated CVD, we have demonstrated that PWV was correlated with insulin, glucose, and BP but was not related to androgen status in overweight women with PCOS. These findings are consistent with previous studies in non-PCOS populations, which have demonstrated that arterial stiffness is correlated with both glycemic control and hyperinsulinemia in diabetic (26,27) and nondiabetic (28,29) subjects. In nondiabetic women, a 25% increase in fasting glucose has been shown to correlate with a 15% (1 sd) decrease in arterial stiffness, whereas an 80% increase in fasting insulin (1 sd) predicted a 7.5% increase in arterial stiffness (28).…”
Section: Discussionsupporting
confidence: 95%
“…In focusing on contributors for accelerated CVD, we have demonstrated that PWV was correlated with insulin, glucose, and BP but was not related to androgen status in overweight women with PCOS. These findings are consistent with previous studies in non-PCOS populations, which have demonstrated that arterial stiffness is correlated with both glycemic control and hyperinsulinemia in diabetic (26,27) and nondiabetic (28,29) subjects. In nondiabetic women, a 25% increase in fasting glucose has been shown to correlate with a 15% (1 sd) decrease in arterial stiffness, whereas an 80% increase in fasting insulin (1 sd) predicted a 7.5% increase in arterial stiffness (28).…”
Section: Discussionsupporting
confidence: 95%
“…Presumably some is AVD, as we have shown that arterial compliance is dependent on classical risk factors for AVD in heal thy subjects and diabetics without clinical evidence of occlusive arterial disease [6,18]. However, another possible contributor to reduce arterial compliance in diabetics is glycation of arterial wall proteins [15], and, for this reason, we prefer to discuss our findings in terms of macrovascular disease rather than AVD.…”
Section: Macrovascular Diseasementioning
confidence: 75%
“…We have previously argued that, where the interest is in macrovascular disease, a study design which allows the range of glucose tolerance from normality, through impairment, to Type II diabetes with no phar macological management, is appropriate for examin ing the determinants of macrovascular disease [18]. It also has the potential for providing a wider range of such determinants.…”
Section: Macrovascular Diseasementioning
confidence: 99%
“…7 Increased aortic PWV has been described by both Wahlqvist 26 and Lehman 27 in otherwise healthy subjects with type 2 diabetes. Salomaa 28 and Emoto 29 have also reported increased carotid artery stiffness in this patient group.…”
Section: Arterial Stiffness and Type 2 Diabetes Mellitusmentioning
confidence: 94%